Dissecting yield and yield-associated traits in Indian mustard (Brassica juncea L.): Insights from correlation and path analysis - Shahina Perween,; Arun Kumar,; Manigopa Chakraborty,; CS Mahto,; MK Barnwal, (Journal of Oilseed Brassica, 2025)
An experiment was conducted to analyze the correlation and path analysis of 12 quantitative traits in 47 genotypes of Indian mustard (Brassica juncea L.), including 13 parent lines, 30 F1 hybrids, and 4 check varieties. The experimental materials were evaluated in a randomized block design with three replications across three different environments: early sown, timely sown, and late-sown. Pooled correlation analysis revealed that plant height, number of secondary branches, main shoot length, siliqua on the main shoot, and maturity exhibited high positive and significant genotypic correlations with seed yield per plant. Phenotypic correlations showed that the number of primary branches per plant, number of secondary branches per plant, and 1000-seed weight had highly significant positive correlations with seed yield per plant. Furthermore, plant height, number of secondary branches per plant, main shoot length, number of siliqua per plant, and number of seeds per siliqua showed high positive and significant phenotypic correlations with seed yield per plant. Path analysis indicated that the number of secondary branches per plant had the maximum positive direct genotypic effect on seed yield, followed by days to maturity, 1000-seed weight, and plant height. The highest direct phenotypic effect on seed yield per plant was exhibited by the number of secondary branches per plant, followed by 1000-seed weight, days to maturity, and number of primary branches per plant.